Reuse of peanut shells and Azolla mixes as a peat alternative in growth medium of Dieffenbachia amoena ‘tropic snow’ - Ali Mahboub Khomami; Mohammad Naghi Padasht; Ali Ajili Lahiji; Fariba Mahtab (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose An experiment was designed to introduce a substitute for peat, which is used in the production of bedding for the cultivation of ornamental plants and is imported and expensive. For this reason, the usability of peanut shells and Azolla, whose accumulation in the environment causes environmental problems, is a major research question. Methods In this work, Dieffenbachia amoena was grown in a growing medium that had substituted peanut shells and Azolla mixes composts (0, 15, 30, 45, 60, and 100 v/v %) for peat. The controls received only peat: perlite (2:1 v/v) without composts. Results It was found that, as the substitution of compost increased, nutrients also increased in the growing medium. Nonetheless, the nutrients led to minor changes in the leaves. As compost increased, the bulk density of the growing media decreased (0.17, 0.16, 0.15, and 0.15 g cm−3). The range of substrate physical properties, such as container capacity, air-filled porosity, and total porosity, was within the recommended range. The 15–100% substitution of compost increased the electrical conductivity and pH of the growing media. The 30% compost treatment led to significant differences in the final height (32.06 cm), trunk diameter (11.66 mm), stem and leaf fresh weight (57.52 g), and stem and leaf dry weight (5.10 g) in comparison with the controls. Conclusions Considering the high price of peat in comparison with compost, replacing peat with 30% compost is economically preferable. Compost was thus found to be a good alternative to peat as an ornamental plants growing medium.